Effectiveness of Psychological and/or Educational Interventions in the Prevention of Anxiety: A Systematic Review, Meta-analysis, and Meta-regression - Moreno-Peral, Patricia; Conejo-Cerón, Sonia; Rubio-Valera, Maria; Fernández, Anna; Navas-Campaña, Desirée; Rodríguez-Morejón, Alberto; Motrico, Emma; Rigabert, Alina; Luna, Juan de Dios; Martín-Pérez, Carlos; Rodríguez-Bayón, Antonina; Ballesta-Rodríguez, María Isabel; et al. (JAMA psychiatry (Chicago, Ill.), 2017)
To our knowledge, no systematic reviews or meta-analyses have been conducted to assess the effectiveness of preventive psychological and/or educational interventions for anxiety in varied populations. To evaluate the effectiveness of preventive psychological and/or educational interventions for anxiety in varied population types. A systematic review and meta-analysis was conducted based on literature searches of MEDLINE, PsycINFO, Web of Science, EMBASE, OpenGrey, Cochrane Central Register of Controlled Trials, and other sources from inception to March 7, 2017. A search was performed of randomized clinical trials assessing the effectiveness of preventive psychological and/or educational interventions for anxiety in varying populations free of anxiety at baseline as measured using validated instruments. There was no setting or language restriction. Eligibility criteria assessment was conducted by 2 of us. Data extraction and assessment of risk of bias (Cochrane Collaboration's tool) were performed by 2 of us. Pooled standardized mean differences (SMDs) were calculated using random-effect models. Heterogeneity was explored by random-effects meta-regression. Incidence of new cases of anxiety disorders or reduction of anxiety symptoms as measured by validated instruments. Of the 3273 abstracts reviewed, 131 were selected for full-text review, and 29 met the inclusion criteria, representing 10 430 patients from 11 countries on 4 continents. Meta-analysis calculations were based on 36 comparisons. The pooled SMD was -0.31 (95% CI, -0.40 to -0.21; P < .001) and heterogeneity was substantial (I2 = 61.1%; 95% CI, 44% to 73%). There was evidence of publication bias, but the effect size barely varied after adjustment (SMD, -0.27; 95% CI, -0.37 to -0.17; P < .001). Sensitivity analyses confirmed the robustness of effect size results. A meta-regression including 5 variables explained 99.6% of between-study variability, revealing an association between higher SMD, waiting list (comparator) (β = -0.33 [95% CI, -0.55 to -0.11]; P = .005) and a lower sample size (lg) (β = 0.15 [95% CI, 0.06 to 0.23]; P = .001). No association was observed with risk of bias, family physician providing intervention, and use of standardized interviews as outcomes. Psychological and/or educational interventions had a small but statistically significant benefit for anxiety prevention in all populations evaluated. Although more studies with larger samples and active comparators are needed, these findings suggest that anxiety prevention programs should be further developed and implemented.